The relationship between surface roughness and fatigue crack growth rate in AA7050-T7451 subjected to periodic underloads. (February 2023) - Field, I.; Dixon, B.; Kandare, E.; Tian, J.; Barter, S.
Highlights: Underloads accelerate the following fatigue crack growth in AA7050-T7451. There is no observable correlation between small-scale systematic surface roughness and growth rate. Large-scale out-of-plane features, such as river patterns, appear to locally slow crack growth. Underloads appear to reduce the size of river patterns, likely diminishing their ability to slow crack growth. Abstract: The accurate prediction of fatigue crack growth rates is necessary to assist with optimising the design, maintenance, and availability of aircraft structures. Roughness induced crack closure is considered by many researchers as an important factor that can impact these growth rates. It has also been suggested that crack closure may be the governing factor behind the accelerative effects of underloads. As such, the focus of this study is on better understanding what correlation there is between the known accelerative effects of underloads, and the local fracture surface roughness of fatigue cracks. Here, specially designed loading spectra are used to quantify the effects of underloads on local fatigue crack growth. Photogrammetry is then used to quantify surface roughness local to the application of the underloads, in order to explore any potential relationship between observed crack growth acceleration and local crack surface roughness. In addition, a general fractographic analysis of the fatigue fracture surface was conducted to understand what correlation there may be between any observed features and the fatigue crack growth rate. It is found that there is little correlation between small-scale surface roughness and the observed acceleration from underloads. However, these is some evidence that large out-of-plane features, such as river patterns, correspond with changes in crack growth rate.